Inequality Crossroads of Mortality: Socioeconomic Disparities in Life Expectancy and Life Span in Mexico Between 1990 and 2015 - Ana C. Gómez-Ugarte; Víctor M. García-Guerrero (Population Research and Policy Review, 2023)
The Mexican health system has been characterized by a mixture of progress and pitfalls, resulting in persistent inequalities. The main causes of death are related to socioeconomic factors reflecting the lack of opportunities regarding access to education, employment, income, and public health services. In this paper, we study the association between social inequality and mortality to assess how population composition by socioeconomic level shapes overall mortality. Socioeconomic information from vital statistics of mortality is used to estimate life expectancy (LE) and lifespan variability by age, sex, and socioeconomic status using three variables: educational attainment, occupation, and access to social security. We also use a decomposition method to separate the effect of changes in population composition by socioeconomic status from changes in mortality by education over changes in LE and lifespan variation. We find that increasing educational attainment and health coverage impact LE positively. The population without formal education and those without access to social security are the worst socioeconomic positions for mortality. The effects of changes in population composition by socioeconomic status is greater for men than for women. Given the amount of contribution from the population structure by socioeconomic status, the implementation of social policies focused on broadening access to tertiary education—which incentivize formal employment and seek to achieve universal health coverage—could boost an increase in the survivorship of Mexican population.
Keywords: 300; Mortality inequality; Life expectancy; Lifespan variation; Socioeconomic inequality; Mexico